CHROMNIUM PICLONAT EFFECTS IN DIET OF MALE RABBITS EXPOSED TO HEAT STRESS ON SOME PRODUCTIVE TRAITS AND BLOOD SERUM PARAMETERS - & Al-Saadi, Hashem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
current study was conducted to determine the effects of Chromium piclonat supplementation on some  productive  traits and serum parameters of male rabbit exposed to heat stress by used electric heaters  ,twenty four male rabbits were randomly divided into four groups 6 for each, first group put in normal suitable climate condition based diet without additional Chromium and kept as positive control group , while The other  three groups exposed to heat stress  , the basal diet was consisted of 0, 300 , and 500 ppb of Chromium piclonate  respectively as a feed additives . All rabbit received feed and water ad libitum, the results showed  that there were Increasing organic Cr supplementation 300 and 500 pbb  of two treated groups resulted in an increase in body weight compared with negative and positive control group , the  serum glucose and cortisone hormone concentrations of both treated groups were decrease, as dietary Cr level increased (P